The combined effect of neutron irradiation and temozolomide on glioblastoma cell lines with different MGMT and P53 status. (September 2020) - Kinashi, Yuko; Ikawa, Tomoyuki; Takahashi, Sentaro
Abstract: Temozolomide (TMZ) is a DNA-alkylating agent used for chemo-radiotherapy of glioblastoma, which is also a target cancer for boron neutron capture therapy (BNCT). Although the DNA-repair enzyme O 6 -methylguanine DNA methyltransferase (MGMT) and the tumor suppressor p53 are mutated in some glioblastoma cells, it remains unknown whether these mutations affect sensitivity to neutron irradiation. We examined sensitivity to neutron irradiation and TMZ in two glioblastoma cell lines: T98G, which is p53-mutant with high levels of MGMT activity; and A172, which is p53–wild-type and has low MGMT activity. T98G cells were more resistant to TMZ treatment than A172 cells, with a 10-fold higher LC50. In A172 cells, TMZ treatment did not change the cell-killing effect of neutron irradiation in the presence of borono-phenylalanine (BPA). By contrast, T98G cells were more resistant to neutron irradiation when BPA was present. These results indicate that DNA repair activity in T98G cells might be higher due to upregulation of MGMT after TMZ treatment. Thus, differences in the MGMT and p53 statuses of glioblastoma cells might predict the effect of combination therapy with BNCT and DNA-alkylating agent. Highlights: The combined effect of neutron radiation and TMZ on glioblastoma cell lines with different MGMT and p53 status was examined. TMZ treatment did not change the effect of neutron radiation in A172 which p53 and MGMT are wild-type. T98G with p53 and MGMT mutated showed more resistant to the neutron radiation when BPA existed.